Ten‐year incidence and prevalence of clinically diagnosed blepharitis in South Korea: a nationwide population‐based cohort study - Rim, Tyler Hyungtaek; Kang, Min Jae; Choi, Moonjung; Seo, Kyoung Yul; Kim, Sung Soo (Clinical & experimental ophthalmology, 2017)
Importance Blepharitis is one of the most common conditions. However, no study has yet evaluated the epidemiology by evaluating a large population‐based sample. Background To evaluate the incidence and prevalence of clinically diagnosed blepharitis in South Korea. Design Nationwide population‐based study. Participants We investigated the Korean National Health Insurance Service‐National Sample Cohort, a representative one million‐sample of the Korean population, for patients diagnosed with blepharitis according to the Korean Classification of Diseases. Methods Annual and overall incidence and prevalence of blepharitis during the study period (2004–2013) were estimated after excluding chronic blepharitis patients, diagnosed during 2002–2003. Sociodemographic factors and comorbidities associated with blepharitis were evaluated using Cox proportional hazard regression. Main Outcome Measures The first occurrence of blepharitis. Results A total of 1 116 363 individuals over 9 698 118 person‐years were evaluated (mean follow up: 8.7 years) from 2004 to 2013. The overall incidence was 1.1 (95% confidence interval, 1.1–1.1) per 100 person‐years. The incidence increased with time (0.9 vs. 1.3 per 100 person‐years, in 2004 and 2013, respectively) and was higher in female patients (1.3 vs. 0.9 per 100 person‐years, respectively). The overall prevalence was 8.1% (95% confidence interval: 8.0–8.1) among subjects aged 40 years or older. Chalazion, gastritis, Sjögren's syndrome, pterygium, rosacea, prostatic hypertrophy, atopy, irritable bowel disease and peptic ulcer were associated with an increased incidence of blepharitis in the multivariable Cox model. Conclusions We found that blepharitis was a relatively common disease and is associated with various ocular and systemic conditions.